A furnace for producing chalcogenide-based alloy and a method for producing thereof - Talib, Zainal Abidin; Sabli, Nordin; Shaari, Abdul Halim; Mat Yunus, W. Mahmood (2012)
The present invention relates to a furnace (100) and a method for producing a chalcogenide-based alloy, characterized by the steps of preparing a powder mixture comprising a metal or a non-metal or a metalloid and a chalcogen in a stoichiometric ratio; pouring the powder mixture into an ampoule (120); sealing the ampoule (120); melting the powder mixture contained in the sealed ampoule (120) in a rotating furnace (100); cooling the powder mixture. The furnace, characterized by a pair of holders (115) coupled to each end of an ampoule (120) containing a chalcogenide-based powder mixture; a cushioning means (116) positioned between the pair of holders (115) and the pair of cover plates (114); a rotating bar (134) connecting the hollow cylindrical body (110) to the motor (140) for rotating said hollow cylindrical body (110). The present invention also relates to a device (200) for producing an evacuated ampoule.